(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Abstracts: The Central Bank is the backbone of the banking system as a whole, and in order to maintain the banking system, one of the most important functions that the Central Bank performs is the function of supervising and controlling banks, with several tools and methods, and one of the most important of these tools is its creation of the function of a compliance observer, which obligated commercial banks to appoint a person in A bank that performs this function according to certain conditions and granting it some powers that would build a sound and compliant banking system. The function of the compliance observer is to follow up on the bank’s compliance with the instructions and decisions issued by the Central Bank and decisions issued by the Board of Directors and to provide advice and advice to the bank in order to correct any violations in the application of those instructions In order to avoid being subjected to financial and administrative penalties by the Central Bank, the research came to show the extent of the impact of the compliance observer and the procedures he takes, which would affect the credit policy and the decision to grant credit, which may avoid the bank exposure to credit risks, which results in the bank’s failure and bankruptcy. To clarify the relationship between the main and sub-research variables, a main hypothesis was formulated and two sub-hypotheses were branched from it. The questionnaire was adopted as a tool in collecting data and information related to the research, and then the results were analyzed and hypotheses proved. Key words: Compliance Monitor ، Banking Compliance، cash credit ، bank default